Islamic Education In Building Student Character - Muhammad Andika Rangkuti; Muhammad Arya Arjuna (Proceeding International Seminar of Islamic Studies, 2019)
This study is entitled The Role of Islamic Education in Building the character of students. Islamic education is the effort of muslim adults who are devoted fully aware and guide the growth of students to build the character of students. The problem that arises in this day and age (millennial) character of students does not meet the criteria in learning Islamic education so that it cannot shape the character of students in the role of Islamic education. Is Islamic education not fulfilled in schools so that the character of students is not like that in the role of Islamic education. The purpose of this study can shape the character of students needed in Islamic education so as to shape the existing character in Islamic education. The method used is library research, qualitative, which is found about the role of education, education, various kinds according to the needs of students.